The Influence of PAI Teachers on the Moral Formation of Early Childhood Students in the KB Taman Ceria Balikpapan - Luthfiyah Amrun; Iskandar Yusuf (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2024)
This research is entitled "The Influence of PAI Teachers on the Moral Formation of Early Childhood Students at KB Taman Ceria Balikpapan". The aim of this research is to assess the influence of PAI teachers on the formation of morals of children aged 5-6 years at KB Taman Ceria Balikpapan. The data in this study were obtained through observations of 30 children, and then the data were analyzed quantitatively. Quantitative analysis was carried out through the t hypothesis test to evaluate the significance of the influence of PAI teacher variables on the formation of children's morals. The results of the analysis show that the PAI teacher variable has a positive and significant influence on the ethical formation of children aged 5-6 years. Hypothesis tests using the t test show that the PAI teacher variable significantly influences the formation of morals in children aged 5-6 years. The results of the t-test showed a significance value of 0.000, lower than the significance level of 0.05, so the alternative hypothesis was accepted. In the results of the linear regression test showing (F= 11,601, P= 0.002), the R-square value showed that 29.3% of PAI teachers had a significant influence on the formation of morals in children aged 5-6 years.